Системах з урахуванням умов спостереження - Стрілкова, Т. О.; Крохмаль, А. В. (ХНУРЕ, 2025)
This work is devoted to the modeling of optoelectronic systems, considering observation conditions. The output signal of such systems represents an additive mixture of background and signal components. The study aims to analyze these factors and develop a simulation approach to improve the accuracy and reliability of optoelectronic system performance. The study presents a model of image formation under different conditions, considering several noise sources. Each mode is characterized by distinct parameters of stochastic processes for both signal and background components, with their ratio also being considered.
Keywords: умови спостереження; optoelectronic systems